Contribution to fusion research from IAEA coordinated research projects and joint experiments. (30th July 2015) - Gryaznevich, M.; Van Oost, G.; Stöckel, J.; Kamendje, R.; Kuteev, B.N.; Melnikov, A.; Popov, T.; Svoboda, V.
Abstract: The paper presents objectives and activities of IAEA Coordinated Research Projects 'Conceptual development of steady-state compact fusion neutron sources' and 'Utilisation of a network of small magnetic confinement fusion devices for mainstream fusion research'. The background and main projects of the CRP on FNS are described in detail, as this is a new activity at IAEA. Recent activities of the second CRP, which continues activities of previous CRPs, are overviewed.